Synergistic effect of alcohols, ketone and water on the yield of soluble compounds and tannins from the barks of Azadirachta indica A. Juss. and Moringa oleifera Lam. - Kwadwo Boakye Boadu; Augustine Sackey Jnr (Masyarakat Peneliti Kayu Indonesia, 2022)
Investigations into the most efficient solvent or solvent mixtures which yield high quantities of tannins for the production of adhesives for the composite industry have been ongoing. However, knowledge on the synergistic effect of ketones, alcohols and water on the yield of soluble compounds and tannins from plants is lacking. Using the Soxhlet extraction method, the synergistic effect of ketone, alcohol and water mixtures in the extraction of soluble compounds and tannins from the barks of Moringa oleifera and Azadirachta indica was examined. Ketone, water and alcohols did not have a definite synergistic effect on the yields of soluble compounds and tannins from the two plants. Mixtures of some solvents, as opposed to their individual solvents, recorded high yield of soluble compounds. The reverse was also observed. Water extract recorded the highest quantity of soluble compounds in M. oleifera while, ethanol-methanol-water mixture (60:20:20) extracted the highest quantity of soluble compounds in A. indica. The mixtures containing either a ketone or the alcohols produced comparatively high tannin yield in A. indica. This trend was not so for M. oleifera. The efficiency of solvents to extract soluble compounds depended mostly on the species.